THE ROLE OF LANGUAGE AWARENESS ON GRAMMAR LEARNING IN INDONESIAN EFL CONTEXT - Andhi Dwi Nugroho; Novita Sumarlin Putri; Nur Aida Arifah (Universitas Sarjanawiyata Tamansiswa, 2018)
The study aimed at investigating the affective role of integrating language awareness into grammar learning in the Indonesian EFL (English as a Foreign Language) context. In the study, questionnaires and interviews on language awareness were given to fifty participants. The findings show that majority of the participants responded to positively change their perceptions of the relationship between learning grammar and language skills. The conclusion underlines the necessity of language awareness in grammar learning in the Indonesian EFL context as well as its future development to facilitate second/foreign language teaching and learning.